Politeness Strategies of President Duterte During Inquest on War on Drugs: Implications on Teaching Communication - Anthony, Jessa Mae C.; Pacate, Dever Jay B.; Tulud, Donnie M.; Barbosa, Estella B. (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to explore and determine the politeness strategies employed by President Rodrigo Roa Duterte during the Inquest of the Blue-Ribbon Committee on the Philippine War on Illegal Drugs. Methodology: A qualitative research design was used, specifically utilizing discourse analysis to examine the politeness strategies employed by President Rodrigo Duterte during the Inquest Proceeding. Data was gathered through video transcription and translation. These data were analyzed using Brown and Levinson’s in 1987 politeness strategy framework to form discourse implications and conclusions. Main Findings: Results revealed that President Duterte employed all the politeness strategies during the Inquest, namely: bald-on-record, negative politeness, positive politeness and off-record strategy. Findings also showed that Duterte’s dominant use of Bald-On Record strategy mirrors his authoritative and assertive nature, projecting a straightforward and decisive leader. Meanwhile, his limited use of Off-Record strategies displays a strategic balance between explicitness and subtlety depending on the audience and context. Novelty/Originality of this study: This study provides valuable insights into the role of politeness strategies in political discourse, offering a deeper understanding of how language shapes power dynamics and public perception in high-stakes settings. This also suggests how educators can meaningfully integrate Duterte’s politeness strategies in discussing persuasive communication, public image construction, and the influence of authority in political settings and debates.